Influencing factors in determining research data repository infrastructure for research data management - Ishak, Iskandar; Ismarau Tajuddin, Nur Ilyana; Jusoh, Yusmadi Yah; Sidi, Fatimah; Abdullah, Rusli; Marhaban, Mohammad Hamiruce; Tugiran, Yusnita; Yusof, Yushaida (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Increasing volumes of data are rapidly being produced by researchers with the advancement of digital technologies. In order to manage these data, a suitable research data repository infrastructure is needed by the higher learning institutions. Apart from storing the data, these data repository need to support the research data life-cycle that include the tasks of data creation, processing, analysis, preservation, access and reuse. The objective of this research is to deeply investigate the influencing factors fordata repository infrastructure in managing research data. A systematic literature review is conducted to perform the investigation where research papers are searched over three electronic journal databases. Selected papers are then analysed and a quality assessment has been conducted to identify the relevant infrastructure for research data repository. As a result, we identified the important components of research data repository infrastructure development.